PENGARUH INFORMATION INTEGRATION INTERNAL TERHADAP SERVICE PERFORMANCE DI ASIACOMMERCE - Ezra Stanley Christianto (Universitas Ciputra Surabaya, 2022)
This study aims to see the relationship between the integration of internal information as a means of information that can have an impact on the company's service performance. The method used in this research is the analysis method in the form of Partial Least Square (PLS) with SmartPLS software. The sample in this study is 38 employees who are currently working in AsiaCommerce. The results of this study indicate that internal information integration has a significant effect on service performance on AsiaCommerce.